Impact of Distributed Leadership of School Heads on Teachers’ Work Satisfaction - Dr. Bushra Salahuddin; Dr. Syed Ahmad Raza Shah Gillani; Dr. Fahmida Bibi (Journal of Religion and Society, 2026)
This descriptive study examined the perceptions of male and female secondary school teachers regarding the distributed leadership practices of school heads and the subsequent impact on teachers’ work satisfaction, conducted within public secondary schools across the southern districts of Khyber Pakhtunkhwa, Pakistan. Using a stratified random sample of 702 teachers (361 male, 341 female) drawn from a population of 8,223, data were collected through a self-administered seven-point Likert scale questionnaire measuring distributed leadership practices and work satisfaction indicators. Descriptive analysis revealed that the largest proportion of teachers (27.7% boys, 26.4% girls) held neutral attitudes toward heads’ distributed leadership, with disagreement responses slightly exceeding agreement among male teachers (38.7% vs. 33.5%) while female teachers showed near parity (36.9% agreement, 36.7% disagreement), indicating a general lack of strong consensus regarding leadership practices. Regarding work satisfaction, overall positive perceptions emerged, with combined agreement categories reaching 51.9% for male and 52.9% for female teachers; however, notable reservations persisted, as 27.7% of male and 32.3% of female teachers expressed mild disagreement. Independent samples t-test results demonstrated no statistically significant difference between male and female teachers’ perceptions of distributed leadership’s influence on work satisfaction (mean scores: 5.35 for males, 5.36 for females; t = 0.1007, p = 0.9198, p > 0.05), leading to acceptance of the null hypothesis. The findings suggest that while distributed leadership is associated with moderate positive work satisfaction across both genders, a substantial neutral and ambivalent stance prevails, and gender does not significantly shape these perceptions. Keywords: Distributed Leadership, Work Satisfaction, Secondary School Teachers, Public Schools, Khyber Pakhtunkhwa, Gender Perceptions, Teacher Attitudes, School Heads.